Association of CYP2E1 gene polymorphisms with bladder cancer risk: A systematic review and meta-analysis. Issue 39 (September 2018) - Yin, Xiangrui; Xiong, Wei; Wang, You; Tang, Wei; Xi, Wang; Qian, Shengqiang; Guo, Yu
Abstract: Background: Human cytochrome P450 (CYP) is an enzyme responsible for the metabolic activation of many carcinogens, including nitrosamines. CYP2E1 represents a major CYP isoform and is expressed in the human urothelial cells. Recent studies have investigated the association of CYP2E1 gene polymorphisms with bladder cancer risk but have shown contradictory results. Hence, we performed a systematic literature review and meta-analysis to assess the association between CYP2E1 gene polymorphisms and bladder cancer. Methods: Systematic literature searches were conducted with PubMed, Excerpt Medica Database, Science Direct/Elsevier, China National Knowledge Infrastructure, and the Cochrane Library up to January 2018 for studies that involved the association of CYP2E1 gene polymorphisms with bladder cancer risk. A meta-analysis was performed with Review Manager and Stata software. Combined odds ratios (ORs) were identified with 95% confidence intervals (CIs) in a random or fixed effects model. Ethics: The protocol was approved by the institutional review board of each study center. Written informed consent will be obtained from all patients before registration, in accordance with the Declaration of Helsinki. Results: Eight studies were identified, including 1733 cases of bladder cancer and 1814 normal controls. Our results illustrated that there are significant associations between CYP2E1 gene polymorphisms and bladder cancer in all genetic models ( P  < .05). The combined ORs and 95% CIs were as follows for each model: additive model [OR 0.56; 95% CI (0.38–0.82)]; dominant model [OR 0.79; 95% CI (0.67–0.93)]; recessive model [OR 0.61; 95% CI (0.41–0.89)]; codominant model [OR 0.80; 95% CI (0.67–0.96)]; allele model [OR 0.75; 95% CI (0.59–0.95)]. A subgroup study showed that there are also significant associations between CYP2E1 gene polymorphisms and bladder cancer in Asian people. However, there are no significant associations between CYP2E1 gene polymorphisms and bladder cancer in Caucasian populations. Conclusions: The present study provides evidence for an association between CYP2E1 gene polymorphisms and bladder cancer progression, and suggests that CYP2E1 gene polymorphisms might be a protective factor against bladder cancer in Asian people. However, studies with larger sample sizes are needed to confirm the correlation between CYP2E1 gene polymorphisms and bladder cancer.